2011
DOI: 10.1016/j.neuroscience.2011.02.008
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of the dopamine transporter 1 gene on P50 sensory gating and its modulation by nicotine

Abstract: Although schizophrenia has been considered primarily a disease of dopaminergic neurotransmission, the role of dopamine in auditory sensory gating deficits in this disorder and their amelioration by smoking/nicotine is unclear. Hypothesizing that individual differences in striatal dopamine levels may moderate auditory gating and its modulation by nicotine, this preliminary study used the mid-latency (P50) auditory event-related potential (ERP) to examine the single dose (6 mg) effects of nicotine (vs. placebo) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 86 publications
2
17
1
Order By: Relevance
“…We postulated that the cholinergic system is one candidate of target enhancement which may be deficient in schizophrenic patients (32). These observations are in line with other studies which showed that the nicotinic system is involved in the regulation of visual information processing (3336) including sensory gating and P50 suppression (9, 37). Interestingly, an alpha 7 receptor agonist improved both p50 gating function and cognition in schizophrenic patients (38).…”
Section: Introductionsupporting
confidence: 93%
“…We postulated that the cholinergic system is one candidate of target enhancement which may be deficient in schizophrenic patients (32). These observations are in line with other studies which showed that the nicotinic system is involved in the regulation of visual information processing (3336) including sensory gating and P50 suppression (9, 37). Interestingly, an alpha 7 receptor agonist improved both p50 gating function and cognition in schizophrenic patients (38).…”
Section: Introductionsupporting
confidence: 93%
“…Antipsychotics, which are primarily dopamine (DA) antagonists, exert little or no effects on cognitive deficits and gating in SZ (Adler et al, 2004), but individual differences in genotypes (DRD2, DAT1) regulating striatal DA (Knott et al, 2010b;Millar et al, 2011) have been shown to affect baseline and nicotine-modulated gating. The relationship between prefrontal DA and cognitive performance has also been described as a U-shaped curve, whereby an excess or an insufficiency can be detrimental (Goldman-Rakic et al, 2000;Williams-Gray et al, 2007;Monte-Silva et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, enhancing effects of nicotine on MMN have been observed in patients with schizophrenia (Dulude et al, 2010). Conversely, the possibility that the phenotype (Fisher et al, 2012b) and genotype (Millar et al, 2011) of patients with schizophrenia influence nicotine's effects has been suggested. Further studies are needed to elucidate the factors affecting nicotine's effects on the automatic change-detecting system.…”
Section: Discussionmentioning
confidence: 99%